2004
DOI: 10.1614/p2002-168d
|View full text |Cite
|
Sign up to set email alerts
|

A role for glutathioneS-transferases in resistance to herbicides in grasses

Abstract: Herbicide resistance is the heritable ability of a weed biotype or population to survive a herbicide application that would effectively kill a susceptible population of the weed. In the U.K. the most widespread and financially important herbicide-resistant weed is blackgrass. Investigations to elucidate the molecular mechanisms conferring herbicide resistance to blackgrass populations have been ongoing for two decades. Although the identification of target site–resistant populations has proved to be relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 43 publications
0
53
0
6
Order By: Relevance
“…Fenoxaprop-P-ethyl and chlorotoluron are herbicide substrates for GST-mediated metabolism in naturally-tolerant cereal crops and NTSR grass populations (Tal et al, 1993;Reade et al, 2004;Cummins et al, 2013). Additionally, preliminary greenhouse trials demonstrated that NBD-Cl at 270 g ha -1 exhibited an optimal increase in atrazine activity (PRE and POST) without displaying visual injury symptoms or secondary phytotoxic effects (data not shown).…”
Section: Effect Of the Gst Inhibitor Nbd-cl On Atrazine Activity Preementioning
confidence: 96%
See 1 more Smart Citation
“…Fenoxaprop-P-ethyl and chlorotoluron are herbicide substrates for GST-mediated metabolism in naturally-tolerant cereal crops and NTSR grass populations (Tal et al, 1993;Reade et al, 2004;Cummins et al, 2013). Additionally, preliminary greenhouse trials demonstrated that NBD-Cl at 270 g ha -1 exhibited an optimal increase in atrazine activity (PRE and POST) without displaying visual injury symptoms or secondary phytotoxic effects (data not shown).…”
Section: Effect Of the Gst Inhibitor Nbd-cl On Atrazine Activity Preementioning
confidence: 96%
“…Along these lines, current research in our laboratory is investigating the hypothesis that similar but distinct GSTbased NTSR mechanisms for atrazine occur in these two waterhemp populations (Evans et al, 2013). The NTSR and MHR mechanisms in grass (Reade et al, 2004;Délye et al, 2011;Cummins et al, 2013) and dicot (Patzoldt et al, 2005;Ma et al, 2013;Scarabel et al, 2015) weeds are providing complex new challenges for weed management and crop production by limiting effective herbicide options available (Preston, 2004;Yu and Powles, 2014). In addition to understanding cross-resistance patterns, genetic and biochemical mechanisms, and the molecular basis for NTSR and MHR in weeds, novel management tools are needed to combat herbicide-resistant weeds or overcome the mechanism(s) that confer resistance to both PRE and POST herbicides (Preston, 2004).…”
Section: Atrazine Postemergence Activity With the Gst Inhibitor Nbd-clmentioning
confidence: 99%
“…O volume de chuvas após a aplicação (Tabela 3) foi suficiente para lixiviar os herbicidas até a região das raízes das plantas, e, nessa situação, eles foram absorvidos juntamente com os nematicidas. Como a detoxificação de produtos primários absorvidos, como herbicidas e nematicidas, é feita por várias enzimas, entre as quais a citocromo P450 monooxigenase (Hatzios & Burgos, 2004;Reade et al, 2004), existente em quantidade limitada no interior da planta, a absorção de herbicida e nematicida provavelmente sobrecarregou o sistema metabólico das plantas, que passaram a manifestar sintomas de intoxicação, classicamente iniciados por clorose seguida por necrose foliar. Significância dos valores de F: ** = 1%, * = 5%, + = 10% e ns = não-significativo.…”
Section: Resultsunclassified
“…For example, glutathione S-transferases (GSTs) are families of multifunctional enzymes that catalyze the conjugation of glutathione to a variety of electrophilic and hydrophobic substrates. GSTs are involved in stress responses, and, in some crop and weed species, some herbicides are detoxified by glutathione conjugation (for reviews, see [75][76][77] ). Herbicide-metabolizing GSTs have been purified and characterized from several crops (for reviews, see 75,78) ).…”
Section: Conferring Non-target Site Herbicide Tolerance By Gtmentioning
confidence: 99%